Binômio arte/vida na arte da performance e a relação sujeito/usura em A plebe do crediário - Isaque Ribeiro (2011)
This research is aimed at studying performance art with the purpose of pointing out and analyzing properties pertaining to its language that relate to the binomial art/life. From this perspective, the concept of performance art and the major characteristics in its emergence as a figure of artistic expression was explored. A hybrid approach of study was adopted, merging theories and practices together with this dissertation, ultimatelyleading to the performance of A Plebe Crediário. This performance, inspired by Oswald de Andrades O Rei da Vela, drawing inspiration from the consumer history of this researcher, with a critical focus on his particular situation as a consumer/debtor, examined the binomial relationship between art and life based on the everyday, autobiographical, political and social aspects present and the historical context in awork of art.